2003
DOI: 10.1086/368334
|View full text |Cite
|
Sign up to set email alerts
|

Suppression byCandida albicansβ‐Glucan of Cytokine Release from Activated Human Monocytes and from T Cells in the Presence of Monocytes

Abstract: The effect of a soluble beta-glucan from Candida albicans (CSBG) on cytokine production by cultured human peripheral blood mononuclear cells (PBMC) was assessed. CSBG induced a slight increase in the spontaneous release of proinflammatory cytokines, such as interleukin (IL)-6, but significantly suppressed endotoxin-induced IL-6 production in cultures of PBMC and monocytes isolated from PBMC. CSBG also suppressed the release of type 1 cytokines, IL-2, and interferon-gamma. These findings suggest that CSBG suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 8 publications
2
37
0
1
Order By: Relevance
“…Similar findings have been described earlier (Kikkert et al, 2007). Conversely, others have found that glucans from C. albicans suppress the LPS-induced IL-6 response (Nakagawa et al, 2003). The biological activity of (1,3)-β-glucans in vertebrates is complex and relates to their origin, size, molecular structure, purity, and cell type or receptor(s) involved (for reviews see Brown, 2006;Goodridge et al, 2009;Reid et al, 2009;Tsoni and Brown, 2008).…”
Section: Referencessupporting
confidence: 73%
“…Similar findings have been described earlier (Kikkert et al, 2007). Conversely, others have found that glucans from C. albicans suppress the LPS-induced IL-6 response (Nakagawa et al, 2003). The biological activity of (1,3)-β-glucans in vertebrates is complex and relates to their origin, size, molecular structure, purity, and cell type or receptor(s) involved (for reviews see Brown, 2006;Goodridge et al, 2009;Reid et al, 2009;Tsoni and Brown, 2008).…”
Section: Referencessupporting
confidence: 73%
“…In some donors, a potentially activated CD3 low CD4 low T cell population was observed that had higher levels of bGR surface expression (data not shown). The presence of bGR has not previously been defined on lymphocytes, although we had detected Dectin-1 mRNA expression in B and T cell lines [10], and there are some reports that their activities can be influenced by these carbohydrates [31,32]. In addition to the recognition of b-glucans, the bGR on these cells may also be involved in mediating interactions with other lymphocytes through recognition of the unidentified endogenous ligand [9,10,13].…”
Section: Distribution Of the Bgr In Human Peripheral Blood Cellsmentioning
confidence: 71%
“…Sherwood et al (44) showed that glucan-phosphate attenuated the induction of LPS tolerance. In addition, ␤-glucan was able to suppress endotoxin-(TLR4)-induced release of proinflammatory cytokine and affect the NF-B pathway (30,43).…”
Section: Discussionmentioning
confidence: 99%